IMPLEMENTATION OF LABORATORY MEASUREMENT OF AIRBORNE SOUND INSULATION BASED ON ISO AND ASTM STANDARDS IN NATIONAL STANDARDIZATION AGENCY OF INDONESIA (BSN) - Bondan Dwisetyo; Maharani Ratna Palupi; Fajar Budi Utomo; Chery Chaen Putri; Dodi Rusjadi; Ninuk Ragil Prasasti; Denny Hermawanto (Badan Standardisasi Nasional, 2021)
The implementation of laboratory measurement of airborne sound insulation based on ISO and ASTM standards was carried out at SNSU BSN. The aim of this work to realize the measurement of airborne sound insulation for several sample tests, where the procedure of the test is performed according to the updated standard ISO 10140 and ASTM E90. Besides, the single number rating also is determined based on ISO 717-1 and ASTM E413. This measurement has been conducted in the two reverberation rooms using pressure method consist of measuring the sound pressure level, measuring the reverberation time, obtaining the sound reduction index (R) or sound transmission loss (STL), and determination of a single-number ratings of the samples test. From the results, some parameter requirements such as the frequency range and the rounding procedure of R or STL influence the measurement result slightly. Subsequently, the significant difference is obtained for the determination of single number rating in the shifting procedure of the reference curve.